KERJASAMA ORANG TUA DAN GURU: KUNCI KEEFEKTIFAN PENDIDIKAN ANAK DI ERA DIGITAL - Felisya Sely Pakiding; Ersa Ersa; Bunga Selda Turu' Allo; Shintya Matandung; Rosiani Dannari (CV. ADIBA AISHA AMIRA, 2025)
Children's education in the digital age requires close cooperation between parents and teachers to ensure children's success and development. Good cooperation between parents and teachers plays an important role in providing holistic education and supporting children's development in the fast-changing digital era. The study discusses the role of parents and teachers in supporting children's education in the digital era and strategies to improve cooperation between them. The research method used is qualitative with a literature study. The result of this study is the role of parents and teachers in children's education in the digital era, parents have an important role in monitoring their children's digital activities, encouraging positive and responsible use of technology and providing emotional support and motivation in children's learning. Teacher's role: Integrate technology in the learning process to improve children's digital skills, act as a facilitator in teaching children about the wise use of technology and communicate openly with parents about the development and challenges in children's education in the digital era. Strategies to improve parent-teacher cooperation include open communication, establishing effective communication channels between parents and teachers through regular meetings, online communication or specialized education apps and encouraging active participation of parents in school activities related to technology and learning in the digital era.